Withania somnifera (Ashwagandha) in neurobehavioural disorders induced by brain oxidative stress in rodents: a systematic review and meta‐analysis. (1st April 2015) - Durg, Sharanbasappa; Dhadde, Shivsharan B.; Vandal, Ravichandra; Shivakumar, Badamaranahalli S.; Charan, Chabbanahalli S.
Abstract Objectives W ithania somnifera has been in use for several thousand years in Ayurveda to treat various neurological disorders. There is, however, not much scientific data on its protective role in neuronal pathology specifically against brain oxidative stress. Hence, an attempt is made in this work for systematic review and meta‐analysis of W. somnifera on neurobehavioural disorders induced by brain oxidative stress in rodents. Methods A systematic search of the effect of W. somnifera on brain oxidative stress‐induced neuronal pathology was performed using electronic databases. The systematic review was performed on neurobehavioural parameters, whereas meta‐analysis of W. somnifera effect was done on oxidative stress markers (superoxide dismutase, catalase, glutathione peroxidase, glutathione and lipid peroxidation), nitrite, protein carbonyl, AchE, ChAT and Ach of rodent brain. Data were analysed using Review Manager Software. Key findings Twenty‐eight studies were selected based upon the inclusion and exclusion criteria. W. somnifera appreciably inhibited the neurological abnormalities due to oxidative stress in rodent brain produced by different physical and chemical stimuli. W. somnifera also significantly restored the altered oxidative and other stress markers in different parts of rodent brain. Summary The systematic review provides scientific evidence for the traditional claim of W. somnifera use in different neurological aliments. However, future clinical trials are mandated to establish the therapeutic efficacy and safety in human beings.